A History of Russian Symbolism. - Peterson, Ronald E. (John Benjamins Pub. Co., 1993)
The era of Russian Symbolism (1892-1917) has been called the Silver Age of Russian culture, and even the Second Golden Age. Symbolist authors are among the greatest Russian authors of this century, and their activities helped to foster one of the most significant advances in cultural life (in poetry, prose, music, theater, and painting) that has ever been seen there. This book is designed to serve as an introduction to Symbolism in Russia, as a movement, an artistic method, and a world view. The primary emphasis is on the history of the movement itself. Attention is devoted to what the Symboli.